2000
DOI: 10.2139/ssrn.2707724
|View full text |Cite
|
Sign up to set email alerts
|

The Determinants of Poverty in Mexico: 1996

Abstract: This study examines the determinants or correlates of poverty in México.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 3 publications
0
1
0
1
Order By: Relevance
“…The same is true in the case of Mexico since Leon (2005), Rascon and Rubalcava (2009) and Garza-Rodriguez et al (2010) all found that lack of education of the household head was a strong predictor of chronic poverty. Since labor is by far the greatest asset of the poor, a low level of education of household members, especially the household head, tends to cause low productivity and low income, which significantly increases the likelihood of the household falling into poverty (Garza-Rodriguez, 2000).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The same is true in the case of Mexico since Leon (2005), Rascon and Rubalcava (2009) and Garza-Rodriguez et al (2010) all found that lack of education of the household head was a strong predictor of chronic poverty. Since labor is by far the greatest asset of the poor, a low level of education of household members, especially the household head, tends to cause low productivity and low income, which significantly increases the likelihood of the household falling into poverty (Garza-Rodriguez, 2000).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Además, se señala que las variables económicas son las que mayor incidencia tienen sobre la probabilidad, pero que dada la naturaleza multidimensional de la pobreza se requieren esfuerzos de política que la ataquen desde los ángulos económico, social y cultural. Garza-Rodríguez (2000) estima un modelo de regresión logística con datos de la ENIGH 1996, utiliza como unidad de análisis los hogares. La variable dependiente es la probabilidad de que un hogar sea pobre en extremo, y un conjunto de variables económicas y demográficas son las variables explicativas.…”
Section: Revisión De La Literaturaunclassified